Characterization of Arabica and Robusta Powder Coffee From Gayo and Toraja Regions Due To Different Brewing Techniques - Rahmawati Rahmawati; Ahmad Suganti (University of Sultan Ageng Tirtayasa, 2026)
The increase in coffee consumers is marked by the growing number of coffee shops. The quality of the best taste of brewed coffee is influenced by the roasting process and brewing technique. The purpose of the study was to determine the taste of coffee based on different types of coffee and brewing techniques. The study used a two-factor sub sampling group randomized design. Factor 1 was coffee type (Gayo arabica, Toraja arabica, Gayo robusta and Toraja robusta), and factor 2 was coffee brewing technique (tubruk and V60). The data obtained were analyzed by ANOVA test using SPSS Version 22. The test was followed by DMRT test (α = 0.05) if it had a significant effect. The results showed that coffee types with different brewing techniques affected total soluble solids, acidity, antioxidant activity, total phenols and organoleptic. The best sample was Toraja robusta coffee type with V60 brewing technique. The resulting quality characteristics are total dissolved solids value of 1.86±0.05 °Brix, pH value of 6.47±0.002, IC50 value of 59.45±0.14 ppm, total phenol value of 1681.38± 8.42 mg/kg GAE, brown color (4.8±1.08) which was slightly preferred (4.8±0.91), strong aroma (5.1± 0.89) which was preferred (5.0± 1.03), non acidic taste (3.9± 0.88), bitter taste (5.5±0.81) which was preferred (5.0±1.11) and caffeine content of 1.41%.